Determination of Fungal Tolerance Index to Heavy Metals and Heavy Metal Resistance Tests - Rosa Calvillo-Medina (Bio-Protocol, 2021)
Fungal metallo-tolerance has been described in different species and plays an important role in bioremediation of contaminated environments. Metallo-tolerance is mainly documented by microdilution assays and agar well diffusion methods using equipment that can be expensive. The tolerance index can be calculated to determine the efficiency of a fungus to degrade and resist heavy metals. The present protocol is based on analyzing the tolerance index and minimum inhibitory concentration of the metallo-tolerance potential of culturable fungi on solid media. This can be calculated by daily measurements of colony size on agar supplemented with different concentrations of heavy metals. This method is an easy approach to determine fungal heavy metal resistance using simple laboratory equipment without spectroscopy.